Kemampuan Guru Melaksanakan Pembelajaran Bahasa Indonesia Berbasis Kurikulum 2013 di SMPN 1 Pujut, Nusa Tenggara Barat - Aa Nunu Aste Lestari; Rusdiawan Rusdiawan; Sudirman Sudirman (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2019)
In this study, we address two purposes: to see the appropriateness between the lesson plan and comprehensible aspects of the 2013 Curriculum components, and appropriateness between teaching preparation made by teachers and the K-13 contents. This study employed qualitative approached applying observation and questionnaire to collect data. Analysis was based upon Miles and Huberman (1994) theories on data collection, data reduction, data display, verification and cioncklusion drawing. Results show that the suitability between completeness of the components lesson plan with Curriculum 2013 is very less appropriate and the percentage suitability between learning process with teacher’s lesson plan 54.34% indicates low appropriateness. Completeness and components of lesson plan are low in seven aspects: indicator formulation, learning objectives, material development, teaching method plan, selection of media and learning resources, plan of teaching stages, and assessment and evaluation process. In addition, the appropriateness of learning process and plan in the lesson plan is perceived in different way dependent in teacher role and context when teaching in the classroom.